Spatial analysis of hypertension in Peruvian adults, 2022 - Hernández-Vásquez, Akram (2023)
Objectives. To perform a spatial analysis of arterial hypertension in the Peruvian adult population to identify geographic patterns with a higher concentration of cases. Materials and methods: A spatial analysis was conducted using data from the Demographic and Family Health Survey (ENDES) 2022. A sample of 29,422 adults was included, and the global Moran’s index and Getis-Ord Gi* analysis were used to evaluate spatial autocorrelation and cluster concentration. Results: The age-standardized prevalence of arterial hypertension was 19.2%. Clusters with a high concentration of arterial hypertension were observed in departments along the Peruvian coast such as Tumbes, Piura, Lambayeque, La Libertad, Ancash, and Lima, as well as in the northern regions of the Highlands. Clusters were also found in the regions of Loreto and Madre de Dios in the Peruvian jungle. Conclusions: This study revealed geographic patterns of arterial hypertension in Peru, with a higher concentration of cases along the Peruvian coast and in certain regions of the Highlands and Jungle. These findings highlight the need to develop strategies for the prevention and control of the disease, especially in the areas identified as high-prevalence clusters.